Advanced Strength and Conditioning : An Evidence-based Approach - Turner, Anthony (Anthony N.); Comfort, Paul (Routledge, 2022)
"Becoming an effective strength and conditioning practitioner requires the development of a professional skills set and a thorough understanding of the scientific basis of best practice. Aimed at advanced students and novice to expert practitioners, the authors explore the latest scientific evidence and apply it to exercise selection and programming choices across the full range of areas in strength and conditioning, from strength and power, speed and agility, to aerobic conditioning. Since the first edition of this text was written there has been extensive research which has expanded the supporting evidence base that provides the theoretical foundation for each chapter. In addition, some areas that were previously under-researched have now been expanded and some key concepts more challenged. Each chapter is written by experts with experience in a wide variety of sports, including both applied and research experience, ensuring this concise but sophisticated textbook is the perfect bridge from introductory study to effective professional practice. While advanced concepts are explored within the book, the coach must not forget that consistency in the application of the basic principles of strength and conditioning are the foundation of athletic development. Advanced Strength and Conditioning: An Evidence-based Approach is a valuable resource for all advanced students and practitioners of strength and conditioning and fitness training"--